Coexistence between Muslims and non-Muslims in Ibn Khaldun’s Sociological Perspective - Ghozali, Muhammad Alfin (Yayasan Pesantren Mahasiswa An-Nur, 2024)
Religion was initially intended to provide solutions for humanity to live a better and more harmonious life. However, in recent decades, numerous conflicts have arisen due to the actions of certain religious adherents in the name of their religious teachings. One of the primary causes of these conflicts is the emergence of radical attitudes, where adherents of one religion view those of other religions as inherently wrong. This has resulted in strained relations between religious communities, fostering hostility rather than understanding. Consequently, various studies and efforts have emerged to promote coexistence among different religious groups. Most of these studies focus on strategies for harmonious interaction between Muslims and non-Muslims but often overlook a critical aspect: the extent to which Islamic teachings permit Muslims to interact with adherents of other religions. This paper explores the perspective of Ibn Khaldun, a pioneering Muslim sociologist, on the concept of coexistence between Muslims and non-Muslims. Specifically, it examines Ibn Khaldun's views on how coexistence can be realized and the limits Islam sets for interactions between its adherents and followers of other religions. Furthermore, the paper analyzes how Ibn Khaldun’s ideas can be applied to contemporary religious contexts. The goal is to position religion, particularly Islam, as a means to address and resolve issues arising from religious diversity rather than being a source of conflict. These efforts are carefully framed within the boundaries established by Islamic Sharia, ensuring that solutions remain faithful to the principles of Islamic teachings.